Design and preparation method of high-speed impact resistant magnesium alloy based on complex multi-phase structure regulation and control

By introducing RE-rich structural units and specific heat treatment processes into magnesium alloys, a multiphase structure is formed, which solves the problem of poor dynamic mechanical properties of magnesium alloys, and achieves high compressive strength and high plasticity under high-speed impact. It is suitable for multiple engineering application.

CN119287236APending Publication Date: 2025-01-10SHANGHAI JIAOTONG UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411430955.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The application of magnesium alloys in the automotive field is limited by their poor dynamic mechanical properties, especially when they are impacted at high speed, which easily forms microcracks and insulating shear belts, resulting in material failure. The prior art is difficult to maintain high plasticity while improving the reinforcement effect. .

Method used

By introducing RE-rich structural units into the magnesium alloy, including Mg matrix grains, LPSO phase and Al2RE phase, and adjusting through a specific heat treatment process, a multiphase structure is formed to improve the high-speed impact resistance of the magnesium alloy.

Benefits of technology

It significantly improves the work hardening ability and compressive strength of magnesium alloy under high-speed impact, avoids the material's failure in early deformation, provides excellent high-speed impact resistance, and maintains high plasticity. It is suitable for transportation, weapons and equipment and aviation. Aerospace field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287236A_ABST
    Figure CN119287236A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of magnesium alloys, and relates to a high-speed impact resistant magnesium alloy design based on complex multi-phase structure regulation and a preparation method thereof. The magnesium alloy provided by the invention has an RE-rich structural unit, and comprises RE-rich Mg matrix crystal grains, an RE-rich LPSO phase and an Al2RE phase. According to the high-speed-impact-resistant multiphase magnesium alloy, magnesium, aluminum and Mg-RE intermediate alloy are melted to obtain magnesium alloy melt; then the magnesium alloy melt is subjected to refining stirring, standing heat preservation and slagging-off treatment, and then a magnesium alloy cast ingot is obtained through casting forming; and finally, the magnesium alloy ingot is subjected to solution treatment. The yield strength of the multi-phase structure is 150-270 MPa, the compressive strength is 500-780 MPa, the fracture deformation is 29%-50% under the impact of a Hopkinson bar at the strain rate of 2000-5000 s <-1 >, and the yield strength, the compressive strength and the fracture deformation of the multi-phase structure are higher than those of commercial magnesium alloy commonly used at present, and the multi-phase structure has huge engineering application value in the fields of traffic and transportation, weaponry and aerospace.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of magnesium alloys, and in particular to the design of a high-speed impact-resistant magnesium alloy based on complex multiphase structure regulation and control and a preparation method thereof. Background Art

[0002] Magnesium alloy is the lightest metal structural material in practical application. It has the advantages of high specific strength and stiffness, easy processing and recycling, and is one of the most ideal structural materials for lightweighting in transportation, aerospace, weaponry and other fields. Although more than 60% of magnesium alloy produced worldwide each year is used in the automotive consumer field, the amount of magnesium alloy used per vehicle is only about 10 kilograms, which is still far from the industry's expectations.

[0003] One of the main factors restricting the application of magnesium alloys in the automotive field is their poor dynamic mechanical properties. There are several main directions to solve this problem: grain refinement, work hardening and second phase particle strengthening. From the perspective of work hardening, taking the currently commonly used AZ series magnesium alloy as an example, the base surface Slip and Twin is its high-speed impact (10 2 ~10 4 s -1 ) process, and as the strain rate increases, The more twins dominate, the lower the work hardening ability of the alloy; such a deformation mechanism causes the grains to quickly adjust from soft orientation to hard orientation during high-speed impact. At this time, since dislocations are more difficult to initiate, the coordinated deformation of twins has been completed, and microcracks or adiabatic shear bands are easily formed in local areas of severe stress and strain concentration, which eventually lead to overall failure of the material. From the perspective of grain refinement, grain refinement by thermoplastic processing is an effective means to improve the strength and plasticity of alloys, but thermoplastic processing usually introduces texture, resulting in anisotropy of dynamic impact properties; another important means is to achieve the purpose of grain refinement by adding elements to allow in-situ self-generated heterogeneous particles as nucleation points during alloy solidification. From the perspective of second-phase particle strengthening, it is generally believed that second-phase particle strengthening will lose plasticity in most cases while strengthening. Therefore, first of all, it is necessary to control its content within a certain range through heat treatment process so that it can exert the strengthening effect as much as possible without significantly damaging the plasticity; secondly, a deformable second phase can be introduced, that is, it can release the stress concentration caused by dislocation pile-up during micro-area deformation through deformation itself, rather than becoming a source of crack initiation in the early stage of alloy deformation due to the incoordination with the deformation of the matrix.

[0004] Therefore, the industry is in urgent need of a magnesium alloy with high high-speed impact resistance, which can refine the grains during the solidification process, activate multiple types of dislocations and twin deformations to improve the work hardening ability when resisting high-speed impact, and further improve the high-speed impact strength with the help of second phase strengthening. Summary of the invention

[0005] The purpose of the present invention is to provide a design of a high-speed impact-resistant magnesium alloy based on complex multiphase microstructure regulation and a preparation method thereof, so as to solve the problems existing in the above-mentioned prior art.

[0006] To achieve the above object, the present invention provides the following solutions:

[0007] One of the technical solutions of the present invention is to provide a high-speed impact resistant multiphase magnesium alloy, wherein the magnesium alloy has a RE-rich structural unit;

[0008] The RE-rich structural unit includes RE-rich Mg matrix grains, RE-rich LPSO phases and Al2RE phases.

[0009] Furthermore, the Al2RE phase is randomly distributed, and the RE-rich LPSO phase is distributed along the grain boundaries or within the grains of the RE-rich Mg matrix grains.

[0010] Furthermore, the RE content RE in the RE-rich Mg matrix grains is ≥ 8wt%.

[0011] Furthermore, the volume fraction of the RE-rich LPSO phase is 0.5% to 25%, the width is 0.10 to 5 μm, and the length is 1 to 100 μm.

[0012] Furthermore, the volume fraction of the Al2RE phase is 0.2% to 5%, and the equivalent circle diameter is 0.1 to 25 μm.

[0013] There is also an inevitable small amount of rare earth-rich second phase between the Al2RE phase, the RE-rich LPSO phase and the RE-rich Mg matrix grains.

[0014] Furthermore, in terms of mass percentage, the magnesium alloy comprises: RE≥8wt%, Al 0.3-4wt%, and the remainder being Mg and unavoidable impurities.

[0015] Preferably, the RE includes one or more rare earth elements.

[0016] Preferably, the Fe content of the unavoidable impurities does not exceed 0.01wt%, the Ni content does not exceed 0.0054wt%, and the Cu content does not exceed 0.005wt%.

[0017] The second technical solution of the present invention is to provide a method for preparing the high-speed impact resistant multiphase magnesium alloy, the steps comprising:

[0018] melting magnesium, aluminum and Mg-RE master alloy to obtain a magnesium alloy melt;

[0019] The magnesium alloy melt is subjected to refining and stirring, standing and heat preservation, and slagging treatment, and then cast and molded to obtain a magnesium alloy ingot;

[0020] The high-speed impact resistant multiphase magnesium alloy is obtained by subjecting the magnesium alloy ingot to solid solution treatment.

[0021] Furthermore, the melting temperature is 680-700°C.

[0022] Furthermore, the refining stirring is performed at 735-745° C. and vigorously stirred for 5-8 minutes.

[0023] Furthermore, the temperature of the static insulation is 730-740° C., and the time is 30-40 minutes.

[0024] Furthermore, the temperature of the slagging treatment is 710-720°C.

[0025] Furthermore, the temperature of the solution treatment is 500-550° C., and the time is 10-48 hours.

[0026] The third technical solution of the present invention is to provide an application of the above-mentioned high-speed impact-resistant multiphase magnesium alloy in transportation, weapon equipment or aerospace.

[0027] The present invention discloses the following technical effects:

[0028] The Mg matrix grains of ordinary commercial magnesium alloys mainly start the basal surface during the high-speed impact resistance process. Slip and Twin coordinated deformation. The RE-rich (RE≥8wt%) Mg matrix grains in the present invention not only promote multi-type dislocation slip, but also inhibit Twin expansion and activation Twins can significantly improve the alloy's work hardening ability under high-speed impact.

[0029] The present invention proves that the LPSO and Al2RE phases formed by adding RE and Al elements can effectively strengthen the Mg matrix and improve the high-speed impact strength under high-speed impact without causing the material to fail in the early stage of deformation. And the content and distribution of the alloy elements and heat treatment processes can be adjusted to be within the optimal performance enhancement range.

[0030] The magnesium alloy based on multiphase structure regulation of the present invention exhibits excellent high-speed impact resistance, has a simple preparation process, and combined with rich rare earth resource reserves, has good industrial application value.

[0031] The high-speed impact resistant multiphase magnesium alloy of the present invention involves the regulation of three RE-rich structural units, including the regulation of the RE-rich Mg matrix grain composition, the regulation of the LPSO phase and the Al2RE component content and distribution, etc. Taking Mg-(Gd, Y)-Al alloy as an example, the mass percentage element composition of the alloy is: (Gd, Y) ≥ 8wt%, Al 0.3-4wt%, and the balance is Mg and unavoidable impurity elements. The Y-rich magnesium matrix grains ensure high plasticity by initiating multi-system slip and further activating {11-21} twins during impact. The LPSO phase and A12Y phase can not only hinder dislocation movement and increase strength, but also deform themselves to release stress concentration caused by dislocation movement without significantly damaging plasticity. The multiphase structure of the present invention is 2000-5000s in the Hopkinson bar. -1 The yield strength under strain rate impact is 150-270MPa, the compressive strength is 500-780MPa, and the deformation is 29%-50%, which are higher than the currently commonly used commercial magnesium alloys. It has great engineering application value in the fields of transportation, weapons and equipment, and aerospace. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0033] Figure 1 The state diagram of the samples of Examples 1 to 3 before and after impact. In the figure, from left to right, 1 is the standard sample, 2 is Example 1 at 3890s -1 After impact, the sample 3 is Example 2 at 3490s -1 After impact, the sample 4 is Example 3 at 4000s -1 Specimen after impact;

[0034] Figure 2 The sample states and microstructure characteristics of AZ31 alloy under different strain rate impact, among which (a) is the state of AZ31 alloy at 1500s -1 and 3500s -1 Sample state after impact, (b) 1400s -1 IPF diagram with a true strain of about 8% after impact, (c) at 1400s -1 BC diagram with a true strain of about 8% after impact;

[0035] Figure 3 The high-speed impact structure and high-speed impact performance of GA91 alloy and the characterization diagram of the interrupted sample structure, where (a) is the metallographic diagram and (b) is the 3890s -1 (c) is the stress-strain curve when the Hopkinson bar strain ring is interrupted by 5% strain and the EBSD microstructure orientation imaging diagram;

[0036] Figure 4 The high-speed impact structure and high-speed impact performance of Mg-8Y-3Gd-1.5Al alloy and the characterization diagram of the interrupted sample structure, where (a) is the metallographic diagram and (b) is the 3490s -1(c) is the stress-strain curve when the Hopkinson bar strain ring is interrupted by 5% strain and the EBSD microstructure orientation imaging diagram;

[0037] Figure 5 The high-speed impact structure and high-speed impact performance of WA101 alloy and the characterization diagram of the interrupted sample structure, where (a) is the metallographic diagram and (b) is the 4000s -1 (c) is the stress-strain curve when the Hopkinson bar strain ring is interrupted by 5% strain. DETAILED DESCRIPTION

[0038] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0039] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0040] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0041] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0042] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0043] In the specific implementation scheme of the present invention, three model alloys of Mg-Gd-Al (Example 1), Mg-Y-Al (Example 3), and Mg-Gd-Y-Al (Example 2) are used as examples.

[0044] The protective gas used in the specific embodiment of the present invention is a mixed gas of SF6 and CO2 in a volume ratio of 1:20 to 1:50.

[0045] Example 1

[0046] Preparation of high-speed impact-resistant multiphase magnesium alloys:

[0047] S1. Prepare pure Mg, pure aluminum and Mg-Y master alloy according to the ratio of Mg-9Gd-1Al (i.e., Gd 9wt%, Al 1wt%), prepare the materials, remove the oxide scale on the surface of the raw materials and then perform preheating treatment (200° C.);

[0048] S2. Under protective gas, heat to 680°C to melt pure Mg, then heat to between 680°C and 700°C, add Mg-Gd master alloy and pure Al, keep warm for 20 to 30 minutes, remove slag on the surface of the melt, and obtain a magnesium alloy melt;

[0049] S3, under protective gas, refining at 735° C. to 745° C., and vigorously stirring for 5 to 8 minutes, and then standing and keeping warm at 730° C. to 740° C. for 30 to 40 minutes to obtain a purified magnesium alloy melt, and then lowering the furnace temperature to 720° C., and after slag removal, casting the alloy melt into a preheated mold to obtain a magnesium alloy ingot;

[0050] S4, the obtained magnesium alloy ingot is subjected to solution treatment at a solution temperature of 515°C and a solution time of 16 hours to obtain a high-speed impact-resistant intracrystalline LPSO phase + A12Gd phase multiphase structure, i.e., a high-speed impact-resistant multiphase magnesium alloy, denoted as GA91 alloy, with a metallographic diagram as shown below: Figure 3 (a) in .

[0051] After testing, the composition of GA91 alloy is as follows:

[0052] Gd 9.22wt%, Al 1.12wt%, inevitable impurities (Fe 0.0021wt%, Ni 0.001wt%, Cu 0.002wt%), and the balance Mg.

[0053] Example 2

[0054] Preparation of high-speed impact-resistant multiphase magnesium alloys:

[0055] S1. Prepare pure Mg, pure aluminum and Mg-Y master alloy according to the ratio of Mg-8Y-3Gd-1.5Al (i.e. Y 8wt%, Gd 3wt%, Al 1.5wt%), prepare the materials, remove the oxide scale on the surface of the raw materials and then perform preheating treatment (200° C.);

[0056] S2. Under protective gas, heat to 680°C to melt pure Mg, then heat to between 680°C and 700°C, add Mg-Y and Mg-Gd master alloys and pure Al, keep warm for 20 to 30 minutes, remove slag on the surface of the melt, and obtain a magnesium alloy melt;

[0057] S3, under protective gas, refining at 735° C. to 745° C., and vigorously stirring for 5 to 8 minutes, and then standing and keeping warm at 730° C. to 740° C. for 30 to 40 minutes to obtain a purified magnesium alloy melt, and then lowering the furnace temperature to 720° C., and after slag removal, casting the alloy melt into a preheated mold to obtain a magnesium alloy ingot;

[0058] S4. The obtained magnesium alloy ingot is subjected to solution treatment at a solution temperature of 540°C for 12 hours to obtain a high-speed impact resistant grain boundary LPSO phase + A12 (Gd, Y) phase multiphase structure, i.e., a high-speed impact resistant multiphase magnesium alloy, denoted as Mg-8Y-3Gd-1.5Al alloy, with a metallographic diagram as shown in FIG. Figure 4 (a) in .

[0059] After testing, the composition of Mg-8Y-3Gd-1.5Al alloy is as follows:

[0060] Y 8.09wt%, Gd 3.03wt%, Al 1.43wt%, inevitable impurities (Fe 0.0034wt%, Ni 0.004wt%, Cu 0.005wt%), and the balance is Mg.

[0061] Example 3

[0062] Preparation of high-speed impact-resistant multiphase magnesium alloys:

[0063] S1. Prepare pure Mg, pure aluminum and Mg-Y master alloy according to the ratio of Mg-10Y-1Al (i.e. Y 10wt%, Al 1wt%), prepare the materials, remove the oxide scale on the surface of the raw materials and then preheat them (200°C);

[0064] S2. Under protective gas, heat to 680°C to melt pure Mg, then heat to between 680°C and 700°C, add Mg-Y master alloy and pure Al, keep warm for 20 to 30 minutes, remove slag on the surface of the melt, and obtain a magnesium alloy melt;

[0065] S3, under protective gas, refining at 735° C. to 745° C., and vigorously stirring for 5 to 8 minutes, and then standing and keeping warm at 730° C. to 740° C. for 30 to 40 minutes to obtain a purified magnesium alloy melt, and then lowering the furnace temperature to 720° C., and after slag removal, casting the alloy melt into a preheated mold to obtain a magnesium alloy ingot;

[0066] S4. The obtained magnesium alloy ingot is subjected to solution treatment at a solution temperature of 550°C for 15 hours to obtain a high-speed impact resistant grain boundary LPSO phase + A12Y phase multiphase structure, i.e., a high-speed impact resistant multiphase magnesium alloy, denoted as WA101 alloy, with a metallographic diagram as shown in FIG. Figure 5 (a) in .

[0067] After testing, the composition of WA101 alloy is as follows:

[0068] Y 10.24wt%, Al 1.02wt%, inevitable impurities (Fe 0.0027wt%, Ni 0.002wt%, Cu 0.003wt%), and the balance Mg.

[0069] Test example

[0070] The commercial AZ31 alloy was used as a control example with the high-speed impact resistant multiphase magnesium alloys prepared in Examples 1 to 3, and the alloy states and organizational characteristics were compared when impacted at different strain rates.

[0071] The high-speed impact resistant multiphase magnesium alloys prepared in Examples 1 to 3 were prepared into samples with a diameter of 8 mm and a height of 6 mm for the Hopkinson bar impact test. The strain rate was controlled at 2000 s -1 -4000s -1 Its performance indicators are shown in Table 1.

[0072] The state diagrams of the samples of Examples 1 to 3 before and after impact are as follows: Figure 1 As shown in the figure, from left to right 1 is the standard sample (sample specification diagram), 2 is Example 1 at 3890s -1 After impact, the sample 3 is Example 2 at 3490s -1 After impact, the sample 4 is Example 3 at 4000s -1 Specimens after impact.

[0073] Table 1

[0074]

[0075] Depend on Figure 1 As can be seen from Table 1, the magnesium alloys prepared in Examples 1 to 3 of the present invention have a Hopkinson bar of 2000 to 4400 s. -1 The yield strength under strain rate impact is 160-230MPa, the compressive strength is 558-633MPa, and the deformation is about 40%, which is higher than the currently commonly used commercial magnesium alloy AZ31.

[0076] Figure 2 The sample states and microstructure characteristics of AZ31 alloy under different strain rate impact, among which (a) is the state of AZ31 alloy at 1500s -1and 3500s -1 Sample state after impact, (b) 1400s -1 IPF diagram with a true strain of about 8% after impact, (c) at 1400s -1 BC diagram with a true strain of about 8% after impact. As can be seen from the figure, the AZ31 alloy has a weak ability to resist high-speed impact. -1 After the impact, the steel broke. As shown in Table 1, the yield strength was 85.8 MPa, the compressive strength was 541.3 MPa, and the elongation was 20.2%. -1 A large amount of Twins.

[0077] Figure 3 The high-speed impact structure and high-speed impact performance of GA91 alloy and the characterization diagram of the interrupted sample structure, where (a) is the metallographic diagram and (b) is the 3890s -1 (c) is the EBSD microstructure orientation image when the Hopkinson bar strain ring is interrupted by 5% strain. It can be seen from the figure that the LPSO phase in (a) is mainly distributed along the crystal. Further measurement by Image software shows that the average width of the LPSO in the crystal is 0.17μm; the length is in the range of 2-15μm, and the volume fraction is 1.4%. The average equivalent circle diameter of Al2Gd is 17.4μm, and the volume fraction is 1.2%. (c) shows that at 5% strain Twins account for 49.1%. 2.2% Although twins dominate, in 3890s -1 This indicates that adding Gd will inhibit Twin formation.

[0078] Figure 4 The high-speed impact structure and high-speed impact performance of Mg-8Y-3Gd-1.5Al alloy and the characterization diagram of the interrupted sample structure, where (a) is the metallographic diagram and (b) is the 3490s -1 (c) is the stress-strain curve when the Hopkinson bar strain ring is interrupted by 5% strain. It can be seen from the figure that the LPSO phase in (a) is mainly distributed along the grain boundary. Further measurement by Image software shows that the average width of the grain boundary LPSO is 2.1μm; the length is in the range of 3-25μm, and the volume fraction is 7.5%. Al2(Gd 0.5 Y 0.5 ) has an average equivalent circle diameter of 15.2 μm and a volume fraction of 1.3%. (c) At 5% strain Twins account for 30.9%. Compared with Example 1, it can be found that in the Mg-(Gd, Y) ≥ 8wt%-Al series alloy, increasing the Y content can promote The twins start.

[0079] Figure 5 The high-speed impact structure and high-speed impact performance of WA101 alloy and the characterization diagram of the interrupted sample structure, where (a) is the metallographic diagram and (b) is the 4000s -1 (c) is the stress-strain curve when the Hopkinson bar strain ring is interrupted by 5% strain and the EBSD microstructure orientation image is shown. Figure 5 It can be seen that the LPSO phase in (a) is mainly distributed along the grain boundaries. Further measurement by Image software shows that the average width of the grain boundary LPSO is 2.3μm; the length is in the range of 4-35μm, and the volume fraction is 11.5%. The average equivalent circle diameter of Al2Y is 12.7μm, and the volume fraction is 1.7%. (c) At 5% strain Twins account for 16.0%, The twin crystals account for 11.7%, which is consistent with the analysis of the effect of Y content in Example 2.

[0080] In addition, Examples 1 to 3 all contain LPSO phase and Al2Re phase, but none of the samples are brittle fractured, but have good work hardening ability while maintaining high plasticity. This shows that both LPSO phase and Al2Y phase are effective strengthening phases in the high-speed impact process.

[0081] From the above analysis, it can be seen that the magnesium alloy based on multiphase structure regulation of the present invention has excellent high-speed impact resistance, and is much higher than the currently used commercial series magnesium alloys. It has great engineering application value in the fields of transportation, weapon equipment, and aerospace. Combined with rich rare earth resource reserves, it has an advantageous prospect for large-scale application.

[0082] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A high-speed impact resistant multiphase magnesium alloy, characterized in that: The magnesium alloy has RE-rich structural units; The RE-rich structural unit includes RE-rich Mg matrix grains, RE-rich LPSO phases and Al2RE phases.

2. The high-speed impact resistant multiphase magnesium alloy according to claim 1, characterized in that: The Al2RE phase is randomly distributed, and the RE-rich LPSO phase is distributed along the grain boundaries or within the grains of the RE-rich Mg matrix grains.

3. The high-speed impact resistant multiphase magnesium alloy according to claim 1, characterized in that: Calculated by mass percentage, the magnesium alloy comprises: RE≥8wt%, Al 0.3-4wt%, and the remainder is Mg and unavoidable impurities.

4. A method for preparing a high-speed impact resistant multiphase magnesium alloy according to any one of claims 1 to 3, characterized in that the steps include: melting magnesium, aluminum and Mg-RE master alloy to obtain a magnesium alloy melt; The magnesium alloy melt is subjected to refining and stirring, standing and heat preservation, and slagging treatment, and then cast and molded to obtain a magnesium alloy ingot; The high-speed impact resistant multiphase magnesium alloy is obtained by subjecting the magnesium alloy ingot to solid solution treatment.

5. The preparation method according to claim 4, characterized in that: The melting temperature is 680-700°C.

6. The preparation method according to claim 4, characterized in that: The refining stirring is carried out at 735-745° C. and vigorously stirring for 5-8 minutes.

7. The preparation method according to claim 4, characterized in that: The temperature of the static insulation is 730-740° C., and the time is 30-40 minutes.

8. The preparation method according to claim 4, characterized in that: The temperature of the slagging treatment is 710-720°C.

9. The preparation method according to claim 4, characterized in that: The temperature of the solution treatment is 500-550° C., and the time is 8-48 hours.

10. Use of the high-speed impact resistant multiphase magnesium alloy according to any one of claims 1 to 3 in transportation, weapon equipment or aerospace.

Citation Information

Patent Citations

  • High-strength cast magnesium alloy and preparation method thereof

    CN102534330A

  • Corrosion-resistant ternary magnesium alloy and preparation method thereof

    CN111270118A

  • High-strength and high-corrosion-resistance ternary magnesium alloy and preparation method thereof

    CN111304510A

  • High-thermal-conductivity magnesium alloy containing high-solid-solubility rare earth elements and preparation method of high-thermal-conductivity magnesium alloy

    CN114351022A

  • Method and device for preparing Mg-Y-Al rare earth magnesium alloy through frequency spectrum multi-dimensional ultrasonic treatment

    CN114752797A